 ×     #### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```
If m belongs to (-1,3) then prove that the roots of x^2-2mx+m^2-1=0 lies in (-2,4)

```
one year ago

```								d> 0: 2 distinct real roots: factors over the reals	d 	d = 0: 1 real root with 2: factors over the reals as a square.Here d=b^2–4ac as given equation is having two roots we follow above rules , First we need to know the basics before solving this questionGiven range -1m values can be (0,1,2)Given Equation x^2–2mx-1=0We need to prove that x values lies in between (-2,4)=====> This means x values can be (-1,0,1,2,3) and they can be complex roots alsox^2–2mx-1=0….substitute m=0 thenx^2–2(0)(x)-1=0x^2=1x=1 or x=-1 ====> It satisfies the given rangenow substitute m=1, Thenx^2–2(1)x-1=0x^2–2x-1=0to find roots use this formulae -b+-suart(b^2–4ac)/2*a=====>2+squart(8)/2 and 2-squart(8)/2 ==> 2(1+squart(2))/2 and 2(1-squart(2))/2On simpler calculation we get roots as 1+squrt(2),1-squrt(2) This lies in the above mentioned range of x(-1,0,1,2,3)Now substitute m=2,Thenx^2–2(2)x-1=0x^2–4x-1=0Again to find roots use the same formulae -b+-suart(b^2–4ac)/2*a2+squart(20)/2 and 2-squart(20)/2 ====> 2(1+squart(5))/2 and 2(1-squart(5))/2so roots are 1+squart(5) and 1-squart(5) ===> This satisfies the desired range but one of the root is not satisfied as the value is just above 3Note : Here to find roots i used formaule -b+-squart(b^2–4ac)/2*awhere b^2–4ac=discriminant
```
one year ago
```							note that aruns ans is absolutely wrong and also assumes that m is an integer. he has probably copied the ans from somewhere.correct method:given x^2 – 2mx + m^2= 1or (x – m)^2= 1or x= m ± 1so, roots are m+1 and m – 1.now, as m lies in ( – 1, 3), so m – 1 lies in ( – 2, 2) and m+1 lies in (0, 4).so overall both the roots lie in the union of ( – 2, 2) and (0, 4).so, the roots of x^2-2mx+m^2-1=0 lies in (-2,4).kindly approve :)
```
one year ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Discuss with Askiitians Tutors

View all Questions »  ### Course Features

• 728 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution  ### Course Features

• 731 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions